2008
DOI: 10.1021/ef7005589
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Biomass Chars Formed under Different Devolatilization Conditions: Differences between Rice Husk and Eucalyptus

Abstract: A comparison between the properties of chars produced by pyrolysis of rice husk and eucalyptus at different temperatures and heating rates has been performed. Low heating rate (LHR) devolatilization experiments were conducted in a fixed bed reactor at temperatures ranging from 600 to 900 °C, while a fluidized bed reactor was used for preparing chars at high heating rate (HHR) and temperatures of 800 and 900 °C. The morphological changes in carbonaceous solids produced in the different thermal treatments were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
102
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(118 citation statements)
references
References 49 publications
10
102
1
2
Order By: Relevance
“…This hypothesis was examined and verified by 29 Si NMR by Freitas et al [9]. Guerrero et al [15] reported no major morphological changes of rice husk under fast heating, and ascribed this observation to a high thermal resistance of rice husk ash, containing mostly silicon compounds. Pottmaier et al [11] concluded that rice husk is less reactive than wheat straw, prepared at temperatures (300e1300 C) under slow and fast heating, and related differences in reactivity to the higher contents of lignin and silicon in the rice husk.…”
Section: Introductionmentioning
confidence: 77%
“…This hypothesis was examined and verified by 29 Si NMR by Freitas et al [9]. Guerrero et al [15] reported no major morphological changes of rice husk under fast heating, and ascribed this observation to a high thermal resistance of rice husk ash, containing mostly silicon compounds. Pottmaier et al [11] concluded that rice husk is less reactive than wheat straw, prepared at temperatures (300e1300 C) under slow and fast heating, and related differences in reactivity to the higher contents of lignin and silicon in the rice husk.…”
Section: Introductionmentioning
confidence: 77%
“…Similarly, due to the lower ash content, black wattle biochar showed higher surface area (241 g/m 2 ) than vineyard (92 g/m 2 ) [29]. Guerrero et al also observed that chars from rice husk devolatilization have lower surface areas compared with those from eucalyptus obtained under similar conditions [30]. On the other hand, the demineralization with acid washing slightly affected surface characteristics of chars, leading to less increase.…”
Section: Char Propertiesmentioning
confidence: 97%
“…In addition to this, the higher heating rate also affects the morphological structure of the solid product. More round pores are formed during the pyrolysis when the temperature increased from 600 °C to 800 °C (Guerrero et al, 2008). This establishes a larger internal cavity and more open structures.…”
Section: The Effect Of Design and Operating Parameters Temperaturementioning
confidence: 98%